Responsivitas Dinas Pengendalian Penduduk Keluarga Berencana Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Sukoharjo dalam Memberikan Perlindungan bagi Korban Kekerasan Perempuan: ( Studi Kasus KDRT di Kalangan Masyarakat Kabupaten Sukoharjo) - Khoirunnisa, Reza Rizqi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The development of domestic violence (KDRT) in Indonesia, especially in Sukoharjo Regency, is still a serious issue. Although there are regulations to protect victims, implementation at the regional level often faces challenges. The Population Control Service, Family Planning, Women's Empowerment and Child Protection (DPPKBP3A) has an important role in providing protection, including quick response in handling cases of violence. This research aims to evaluate the responsiveness of DPPKBP3A in protecting victims of domestic violence through observation, interviews and documentation. The research results show that the responsiveness of DPPKBP3A is not optimal, with three of the six service indicators—speed, accuracy and thoroughness—not yet met. However, indicators of ability to respond to the community, timeliness of service and responding to complaints have been implemented well.